IPP-constructions in Bavarian and Alemannic in comparison. - Schallert, Oliver (Bavarian Syntax. Contributions to the Theory of Syntax., 2014)
I present an analysis of verb order variation occurring with so called “substitute infinitive” constructions in (Austrian) Alemannic and Bavarian, which hinges on three central ideas: First, following the standard assumption that the unexpected morphological marking on the verb is an effect of conflict resolution between morphological and syntactic constraints (e.g. Schmid 2000, 2005), I show that these dialects employ at least three different “repair strategies” that rely on morphological underspecification of the participle. Second, the different serialization patterns that can be observed show a clear asymmetry in that left-branching structures never allow nonverbal interveners (verb projection raising), while this is always an option for right-branching structures. I show how these differences can be derived by a modified version of the Branching Constraint (Haider 2003, 2013). Taking the direction of licensing (Statusrektion ‘status government’ in Gunnar Bech’s 1955 seminal work) that a verbal head employs to be open for (micro-)parametric variation, I demonstrate how differences between the two dialect groups, but crucially also speaker-oriented variation (“idiolectal variability” in the sense of Cornips 2009) can be analyzed with Stochastic Optimality Theory (StOT), cf. Boersma and Hayes (2001), Bresnan, Deo, and Sharma (2007). As Gen(erator), Williams’ (2003, 2004) formal language CAT shall be used, which offers a very simple means for analyzing complex predicates through functional composition.<br